2020
DOI: 10.3390/nu12030611
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Attenuates Lipopolysaccharide-Induced Acute Lung Injury by Regulating NLRP3 Inflammasome and NRF2 Signaling

Abstract: Glycine supplementation has been reported to alleviate lipopolysaccharide (LPS)-induced lung injury in mice. However, the underlying mechanisms responsible for this beneficial effect remain unknown. In the present study, male C57BL/6 mice were treated with aerosolized glycine (1000 mg in 5 mL of 0.9% saline) or vehicle (0.9% saline) once daily for 7 continuous days, and then were exposed to aerosolized LPS (5 mg in 5 mL of 0.9% saline) for 30 min to induce lung injury. Sera and lung tissues were collected 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Concurrently, exogenous glycine increased Nrf2 signaling, activating cellular oxidative stress responses such as HO-1. Together, exogenous glycine attenuates IL-1β production by decreasing the expression of NLRP3 inflammasome components [114]. Collectively, these studies demonstrate that the diverse pool of cellular amino acids has the ability to positively and negatively regulate the NLRP3 inflammasome ( Figure 2).…”
Section: Amino Acid Metabolismmentioning
confidence: 77%
See 1 more Smart Citation
“…Concurrently, exogenous glycine increased Nrf2 signaling, activating cellular oxidative stress responses such as HO-1. Together, exogenous glycine attenuates IL-1β production by decreasing the expression of NLRP3 inflammasome components [114]. Collectively, these studies demonstrate that the diverse pool of cellular amino acids has the ability to positively and negatively regulate the NLRP3 inflammasome ( Figure 2).…”
Section: Amino Acid Metabolismmentioning
confidence: 77%
“…Lastly, the amino acid glycine was shown to inhibit NLRP3 inflammasome activation in a model of lung injury [114]. Mechanistically, exogenous glycine was found to attenuate LPS induced NF-κB activation, without altering protein abundance of the upstream proteins TLR4 or MyD88.…”
Section: Amino Acid Metabolismmentioning
confidence: 96%
“…NLRP3 inflammasome is activated in diversified lung injuries. For instance, Zhang et al, 2020; showed that Glycine prevents LPSinduced lung injury by inactivating NLRP3 and enhancing Nrf2 (Sun et al, 2018). Other scholars have found that Diosmetin attenuates LPS-induced acute lung injury by activating Nrf2 and inhibiting NLRP3 (Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in glutamate during ischemic conditions of glucose deprivation and hypoxia induces ER stress, Ca 2+ influx, and TXNIP expression, resulting in NLRP3 inflammasome activation [ 102 ]. The amino acid glycine was found to attenuate IL-1β production by decreasing the expression of NLRP3 inflammasome components [ 103 ]. The best-characterized stimuli of the NLRP3 inflammasome is ATP (nucleotide-containing DAMP), which regulates it in a manner beyond the initial upregulation of IL-1β by NF-κB [ 104 ].…”
Section: Nlrp3 Inflammasome In Obesity-associated Metabolic Syndromentioning
confidence: 99%